Noninvasive sublingual microvascular imaging reveals sex‐specific reduction in glycocalyx barrier properties in patients with coronary artery disease. Issue 2 (20th January 2020) - Brands, Judith; Hubel, Carl A.; Althouse, Andrew; Reis, Steven E.; Pacella, John J.
Abstract: Background: Risk factors for coronary artery disease (CAD) have been associated with endothelial dysfunction and degradation of the endothelial glycocalyx. This study was designed to compare sublingual microvascular perfusion and glycocalyx barrier properties in CAD patients and controls using noninvasive side stream darkfield imaging. Methods: Imaging of the sublingual microvasculature was performed in 52 case subjects (CAD confirmed by left heart catheterization) and 63 controls (low Framingham risk score). Red blood cell (RBC) filling percentage and functional microvascular density, measures of microvascular perfusion, and perfused boundary region (PBR), an index of glycocalyx barrier function, were measured in microvessels with a diameter ranging from 5–25 µm. Results: RBC filling percentage was lower in patients with CAD compared to controls ( p  < .001). Functional microvascular density did not differ between groups. The overall PBR was marginally greater in the CAD group compared to the control group ( p  = .08). PBR did not differ between male CAD cases and controls ( p  = .17). However, PBR was greater in females with CAD compared with female controls ( p  = .04), indicating reduced glycocalyx barrier function. This difference became more pronounced after adjusting for potential confounders. Conclusions: Our data suggest that patients with CAD are characterized by a reduction in percentage of time microvessels are occupied by RBCs. In addition, CAD is significantly associated with impaired sublingual microvascular glycocalyx barrier function in women but not men. More research is needed to determine the significance of peripheral microvascular dysfunction in the pathophysiology of CAD, and how this may differ by sex. Abstract : We found that both males and females with coronary artery disease (CAD) have significantly impaired sublingual microvascular perfusion reflecting a reduced microvascular tube hematocrit. Furthermore, females with CAD exhibited a significant reduction in glycocalyx barrier properties compared to female controls, whereas males with CAD showed no difference in glycocalyx barrier function, suggesting a sex‐specific reduction in glycocalyx barrier properties.